FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN IBU HAMIL TRIMESTER III DALAM KELAS IBU HAMIL DI WILAYAH KERJA PUSKESMAS BANGLI TAHUN 2022 - Luh Eka Pratiwi; Ni Komang Yuni Rahyani; Listina Ade Widya Ningtyas (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2023)
Efforts to reduce MMR and IMR by increasing insight and knowledge about health services for pregnant women, maternity, postpartum, family planning services, and BBL care provided through pregnant women's class activities that include mothers and their families. To find out the factors that influence the participation of pregnant women in the third trimester in the implementation of classes for pregnant women in the Bangli Community Health Center working area in 2022 is the aim of this research. The method used in the research is correlational with a cross sectional research design. The research respondents, namely 35 pregnant women in the third trimester, used primary data using questionnaire sheets. The factors in question include knowledge, education, age, occupation, parity and source of information. Using the chi square test, it was found that 23 pregnant women who took part in the pregnancy class had good knowledge with a value of p=0.002, and 18 people had secondary education with p value = 0.438, 31 people are not at risk with a p value = 0.292, 18 people do not work with a p value = 0.00, 26 people are multigravida with a p value = 0.244, 27 people have a source of information with a value of p=0.002. The conclusion of this research is that there is a relationship between knowledge, work and sources of information and participation in classes for pregnant women, while education, age and parity have no relationship with participation in classes for pregnant women.